A facile chemical route for recovery of high quality zinc oxide nanoparticles from spent alkaline batteries. (May 2016) - Deep, Akash; Sharma, Amit L.; Mohanta, Girish C.; Kumar, Parveen; Kim, Ki-Hyun
Highlights: A simple technique is proposed for the recovery of high purity zinc oxide nanoparticles from spent alkaline Zn–MnO2 batteries. One-pot chemistry is developed with minimum chemical requirements at moderate temperature conditions. ZnO nanoparticles of around 5 nm size are obtained. Separated MnO2 is also pure. Abstract: Recycling of spent domestic batteries has gained a great environmental significance. In the present research, we propose a new and simple technique for the recovery of high-purity zinc oxide nanoparticles from the electrode waste of spent alkaline Zn–MnO2 batteries. The electrode material was collected by the manual dismantling and mixed with 5 M HCl for reaction with a phosphine oxide reagent Cyanex 923® at 250 °C for 30 min. The desired ZnO nanoparticles were restored from the Zn-Cyanex 923 complex through an ethanolic precipitation step. The recovered particle product with about 5 nm diameter exhibited fluorescent properties (emission peak at 400 nm) when excited by UV radiation (excitation energy of 300 nm). Thus, the proposed technique offered a simple and efficient route for recovering high purity ZnO nanoparticles from spent alkaline batteries.